Do they want contact with us? The role of intergroup contact meta‐perceptions on positive contact and attitudes. (16th February 2020) - Stathi, Sofia; Di Bernardo, Gian Antonio; Vezzali, Loris; Pendleton, Samantha; Tropp, Linda R.
Abstract: This research examined the role of contact meta‐perceptions on positive intergroup contact and outgroup attitudes. Specifically, perceptions of the ingroup's and outgroup's desire for intergroup contact were simultaneously tested as predictors of intergroup contact and outgroup attitudes. Three correlational studies were conducted in three distinct contexts, international students' view of British students, general public views of people with schizophrenia, and both Muslims' and non‐Muslims' views of one another. Among these three intergroup relationships, the role of outgroup contact meta‐perceptions was consistently highlighted as predictor of intergroup contact. In stark contrast, ingroup contact meta‐perceptions did not emerge as a significant predictor of contact. Intergroup contact then predicted outgroup attitudes (Studies 1, 2, and 3) and stereotyping (Studies 2 and 3) via reduced anxiety (Studies 2 and 3). The results demonstrate the importance of explicitly highlighting outgroups' openness for intergroup interactions and are discussed in the context of intergroup relations literature.